Dampak Pandemi Covid-19 Terhadap Pergerakan Pasar Modal di Indonesia - Lutfiati Rachmania Zaeni; Doni Putra Utama (Pusat P2M Politeknik Negeri Batam, 2022)
This study aims to find empirical evidence regarding differences in trading volume, trading frequency, and market capitalization in the movement of the Indonesian capital market before and after COVID-19. This research is quantitative with a cross-section method with different hypothesis tests using paired sample t-test. The population in this study is 48 companies that are members of the Indonesia Stock Exchange in semester 1 of 2019 and 2020 in the consumer goods industry sector, determined by the purposive sampling technique. This study's results indicate differences in the frequency of stock trading before and after the COVID-19 pandemic. However, there is no difference in trading volume before and after the COVID-19 pandemic. Then, there is also no difference in stock market capitalization before and after the COVID-19 pandemic.